Analisis Yuridis Perlindungan Hukum Terhadap Konsumen Produk Pangan dalam Perspektif Undang-Undang No.17 Tahun 2023 Tentang Kesehatan - Putriana, Rosi; Linda Sitanggang, Maura; A.Makbul (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Consumer protection, especially in the food industry, plays an important role in maintaining the quality and safety of products circulating in the market. In the context of advances in science and technology, especially in the food sector, the challenges of ensuring safe and quality products are increasingly complex. Therefore, legal protection for food consumers is vital to protect consumer interests and encourage business actors to be responsible for the products they produce. The following is a discussion related to the importance of legal protection for food consumers, the legal channels that can be taken, and compliance with applicable standards. Objectives of Legal Protection for Food Consumers Legal protection for food consumers aims to: Protect consumer interests by supervising and controlling negligence on the part of businesses in regulating food products circulating in the market. Provide a sense of security for consumers regarding the quality and safety of the products they consume. Encourage business actors to be responsible for maintaining product quality, and ensure that the products produced are in accordance with applicable standards without disrupting their operational activities. Legal Channels That Consumers Can Take When faced with food products that do not meet standards, consumers can choose two legal channels to resolve the problems that arise. Compliance with Food Safety and Quality Standards Compliance with food safety, quality, and nutrition standards stipulated in Law Number 17 of 2023 concerning Health. Several important provisions in this law related to food safety standards include: Article 146 paragraph 1 states that every individual responsible for the production, processing, and distribution of food and beverages must meet applicable standards and requirements related to safety, quality, and nutrition. This aims to ensure that products circulating in the market do not harm consumers. The halalness of food products is also an important part of this regulation, where food products must comply with the provisions stipulated in the legislation, which may include halal inspection or certification for products circulating in the market